Komunikasi Ritual Suroan pada Masyarakat Suku Jawa di Kota Bengkulu - Siroy Kurniawan (Institut Agama Islam Negeri Bengkulu, 2019)
Traditional rituals wrapped in religious nuances are quite diverse in Indonesia. One of the traditional rituals that is still preserved today is the suroan ritual. The suroan ritual is a memorial to the annual agenda in welcoming the Islamic newyear. Suroan in the Javanese calendar coincides with the calendar of the Islamic Hijri newyear falling in the month of Muharram. The suroan ritual carried out by the Javanese pzeople is still preserved. Like suroan in Bengkulu, Javanese people who have moved for decades from Java to Bengkulu, they still carry out this Suroan warning with complete symbols. The symbols used in the Suroan ritual have profound meanings. The meaning contained in these symbols becomes one of the cultural propaganda communication movements wrapped in religious nuances. The meanings contained include: 1). Takir Plontang, is interpreted as a form of solidarity, interrelation with one another among Muslims to maintain harmony, peace and blessings in life. 2). Sodo, symbolizes the bond of the two sentences of shahada which gives peace and blessings in Islam. 3). Janur Kuning, the philosopher that the yellow palm signifies the existence of light, an illumination for Muslims. The local community feels a strong Islamic ukhuwah, looking after each other, protecting and protecting one another. This research provides an explanation to the public that traditional rituals have meaning that is full of important lessons in life. So that people should continue to preserve traditional rituals as they should